Relevance Of Sensor And Chemical Technology In Water Quality Monitoring - et.al, Richa Khare (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper is related to the monitoring of water quality and others problem related to water distribution systems for common people. Our target is to develop such sensors and other chemical methods to calculate the exact value of different parameters related to water at A very low cost. In this paper, we present our studies about pH value, conductivity, temperature, turbidity, BOD and DO. The results of our experiments show that the minimum value system is efficient of monitoring these high impact contaminants at fairly low concentrations.